Comparison of types, contents and antioxidant abilities of phenols from by-products in grape wine-making - WANG Yong, ZHANG Lifeng, QIANG Feng, ZHOU Xiaofang, LI Chaoyu, ZHANG Jun (Zhongguo niangzao)
The phenols were extracted from the seeds, pericarps and stems of 4 kinds of grape (Muscat Hamburg, Italian Riesling, Merlot and Cabernet Sauvignon) wine-making by-products, the types, contents of phenols compounds and their scavenging abilities to 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals were compared. The results showed that the contents of total phenols, total flavonoids and tannins in the seed of Muscat Hamburg were the highest, which were 49.5 mg/g, 30.3 mg/g, 1.13 mg/g, and the scavenging abilities to DPPH and ABTS radicals were the strongest, which were 164 μmol Trolox/g, 294 μmol Trolox/g, respectively. The resveratrol content in the stem of Muscat Hamburg was the highest (1 794 μg/g). The contents of total phenols, total flavonoids, tannins and the scavenging abilities to DPPH and ABTS radicals in different parts of grapes were as follows: grape seeds>grape stems>grape pericarps, the contents of resveratrol were as follows: grape stems>grape seeds>grape pericarps. The contents of total phenols, total flavonoids, tannins, resveratrol and the scavenging ability to DPPH and ABTS radicals in different varieties of grapes were as follows: Muscat Hamburg>Italian Riesling>Merlot>Cabernet Sauvignon. The contents of gallic acid, catechins, epicatechins, and caffeic acids in Muscat Hamburg grape seeds were the highest, which were 44.43 μg/g, 73.23 μg/g, 97.41 μg/g, 45.12 μg/g, respectively, and the content of ferulic acids in the Muscat Hamburg stems were the highest, which were 13.3 μg/g. The antioxidant activities of phenols in wine making by-products had the highest correlation with the content of total flavonoids.